Recent Advancements in the Nanomaterial Application in Concrete and Its Ecological Impact - Haleema Saleem (MDPI AG, 2021)
At present, nanotechnology is a significant research area in different countries, owing to its immense ability along with its economic impact. Nanotechnology is the scientific study, development, manufacturing, and processing of structures and materials on a nanoscale level. It has tremendous application in different industries such as construction. This study discusses the various progressive uses of nanomaterials in concrete, as well as their related health risks and environmental impacts. Nanomaterials such as nanosilica, nano-TiO2, carbon nanotubes (CNTs), ferric oxides, polycarboxylates, and nanocellulose have the capability to increase the durability of buildings by improving their mechanical and thermal properties. This could cause an indirect reduction in energy usage and total expenses in the concrete industry. However, due to the uncertainties and irregularities in size, shape, and chemical compositions, some nanosized materials might have harmful effects on the environment and human health. Acknowledgement of the possible beneficial impacts and inadvertent dangers of these nanosized materials to the environment will be extremely important when pursuing progress in the upcoming years. This research paper is expected to bring proper attention to the probable effects of construction waste, together with the importance of proper regulations, on the final disposal of the construction waste.